2019
DOI: 10.3389/fpsyg.2019.01159
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Parental Control on Cyber-Victimization in Adolescence: The Mediating Role of Impulsivity and High-Risk Behaviors

Abstract: The aim of this work is to analyze the relationship between parental control and cyber-victimization in adolescence, considering the possible mediating effect of impulsivity, and high-risk internet behavior. To that end we analyzed the responses of 3360 adolescents aged between 11 and 18 ( M = 14.02; SD = 1.40), from Asturias (Spain), to four previously validated questionnaires in order to measure the level of parental control over the use of the internet (restrict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
18
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 40 publications
3
18
0
5
Order By: Relevance
“…Not so in the general mood, the increase in this variable score implied lower perceived in in likelihood of violent behavior. Therefore, the results of the study allow taking into account preventive actions aimed at improving school life, alleviating difficulties in stress management, adaptability, and interpersonal relationships [14,15,17,18,19,20,24], and, above all, to prevent them from being associated with other risky behaviors, such as drug consumption or involvement in antisocial behavior [30,31].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Not so in the general mood, the increase in this variable score implied lower perceived in in likelihood of violent behavior. Therefore, the results of the study allow taking into account preventive actions aimed at improving school life, alleviating difficulties in stress management, adaptability, and interpersonal relationships [14,15,17,18,19,20,24], and, above all, to prevent them from being associated with other risky behaviors, such as drug consumption or involvement in antisocial behavior [30,31].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, training or education in EI issues should be integrated into bullying and cyberbullying education. Among preventive actions, emotional regulation can be considered a valuable resource [24]; self-oriented personal competencies [27], stimulating socially desirable and prosocial behavior [28,35,39]; peer tutoring [38]; mitigation of ethno–cultural bullying [29]; it is essential to take into account family functioning for the positive [20,30]; the fundamental role of teachers in the prevention of bullying and cyberbullying; as well as the importance of improving security and climate in schools and other settings [31,37]. According with Save the Children [5] it is everyone’s responsibility to eradicate violence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Más allá de los estudios descriptivos, son necesarias investigaciones que avancen información sobre factores causales o al menos correlacionales. Hasta el momento las investigaciones han centrado su atención en los factores personales y los referidos al contexto escolar y la calidad de la convivencia, recibiendo menor atención el contexto familiar y sus factores diferenciales (Álvarez-García et al, 2019). Algunos trabajos en este campo señalan el importante papel de la comunicación intrafamiliar y, particularmente, apuntan a la revelación filial como uno de los elementos diferenciales de la calidad de la convivencia familiar.…”
Section: Introductionunclassified
“…Meanwhile, several studies, including systematic reviews of comorbidity studies [(e.g., (2)(3)(4)], have shown a strong link between ADHD and Internet Gaming Disorder (IGD), suggesting that online gaming and other online activities may actually be a causal or contributing factor to developing ADHD. Similarly, a meta-analytic study showed that digital therapies for children and young people's mental health were promising (5), but also fueled anxieties in parents who could not reconcile encouraging their children to use the internet and games for treatment when they were constantly pressing them to reduce screen use, due to concern about the negative impact of digital media on children's emotional and social wellbeing (6,7).…”
Section: Introductionmentioning
confidence: 99%